Analysis of measurement accuracy of Zn–Fe alloy coatings under two take-off angles. (November 2022) - Xu, Wei; Wang, Yang; Yang, Hui
Abstract: The multilayer structure of the zinc-iron alloy coating leads to the online measurement accuracy of coating weight (mass) being slightly inferior to that of the zinc coating. Through offline and online comparative analysis of 20 samples with a weight of zinc-iron alloy coating between 30 and 50 g/m 2, the average error of the sum of two-sided averages up to 8 g/m 2 . By studying the characteristic X-ray fluorescence intensity at two take-off angles, we established a calibration curve of 30–50 g/m 2, and proposed a fast measurement method based on coordinate projection. Under the disturbance of zinc-iron alloy phase structure, the measurement error was ±1 g/m 2 18 samples test manifest the average error of coating weight measurement reduced from 8 g/m 2 to 0.56 g/m 2 . The accuracy increased from 91.28% to 98.64%. Highlights: A curve for simultaneous measurement of coating weight and Fe content is obtained. Making better recognition rate of Fe content in the two take-off angles based method. Measurement accuracy of the weight of Zn–Fe alloy coating is significantly improved. MCNP simulation avoids errors introduced by instruments or samples preparation. Coordinate projection reduces complexity and time of online measurement.